Mixtoscutella Grischenko & Gordon & Taylor & Kuklinski & Denisenko & Spencer-Jones & Ostrovsky 2022, n. gen. - Grischenko, Andrei V.; Gordon, Dennis P.; Taylor, Paul D.; Kuklinski, Piotr; Denisenko, Nina V.; Spencer-Jones, Mary E.; Ostrovsky, Andrew N. (Zenodo, 2022)
Genus Mixtoscutella n. gen. Type species: Cellepora ovata Smitt, 1868, by original designation. Diagnosis. Colony encrusting, multiserial, unilaminar.Frontal shield mixed, comprising a much-reduced umbonuloid area beneath suboral avicularium, corresponding externally to suboral avicularium, and extensive, uniformly pseudoporous lepralioid area. Primary orifice with or without lyrula, with condyles. Secondary orifice cormidial, with very low peristome. Suboral adventitious avicularium always present. Large adventitious avicularia present in some species. Ovicell hyperstomial, often becoming less prominent due to secondary calcification overgrowing ooecium; with pseudopores. Mural pore chambers and multiporous septula present. Basal wall fully calcified, without protuberances. Etymology. The name refers to the mixed nature of the frontal shield. Species included. Mixtoscutella ovata (Smitt, 1868a), M . ussowi (Kluge, 1908a), M . cancellata (Smitt, 1868a), M . harmsworthi (Waters, 1900), and M . androsovae (Gontar, 1979). Remarks. Apart from two species examined in detail ( M . ovata and M . ussowi ) and transferred from Rhamphostomella (Figs 27, 28), we illustrate here three other taxa, including two little-known species (Fig. 29), that display a combination of characters (mixed frontal shield and suboral avicularium) warranting their placement in Mixtoscutella . Mixtoscutella androsovae (Gontar, 1979) [= Smittina androsovae Gontar, 1979 (p. 244, fig. 4)] is known only from its type locality at Cape Nerpochka on the Pacific side of Simushir Island, middle Kuril Islands, from 30 m depth (paratype, ZIRAS 2 /43716) (Fig. 29A–C). The high-boreal-Arctic species, M . harmsworthi (Waters, 1900) [= Schizoporella harmsworthi Waters, 1900 (p. 65, pl. 9, figs 10–12)], widely distributed in Arctic seas (see Kluge 1962 for details) has been detected in Avacha Gulf, eastern Kamchatka (ZIRAS 52/50568, KIENM Collection, RV Nazarovsk , Stn 141, 11 May 1988, 53°41.0ʹ N, 160°04.0ʹ E, depth 75 m) (Fig. 29D–F). The rarely reported M . ...